Análisis de inversión y reducción de costos en un contexto de lean accounting - Colazo, Jerónimo Alberto (2023)
This paper develops and explains step by step how a company used lean accounting tools to identify cost savings and how these savings are integrated into a project investment evaluation. Little is known about the use of lean accounting tools in small and medium-sized companies operating in regional economies of Latin America, and this study is designed to continue expanding our knowledge of the subject. The tool used is value stream mapping and it is shown how it allows to identify cost savings, which is the first stage to calculate the recurring cash flows that is a critical building block of traditional project evaluation tools. This study is based on a real case that links aspects of production method and improvements applying lean manufacturing and financial indicators of the project. The development of the investment project allowed the company under study to improve delivery times, operation safety, production stability, process automation and increase the overall processing capacity of the plant. It also made visible sources of inefficiency in the current process that impacted parts handling, operating costs, rework, and direct labor.